ASPP2 Coordinates ERS-Mediated Autophagy and Apoptosis Through mTORC1 Pathway in Hepatocyte Injury Induced by TNF-α - Yao, Jia; Yang, Hui; Wang, Han; Shi, Honglin; Jiao, Yan; Zhang, Ying; Chen, Dexi; Shi, Hongbo (Frontiers in Pharmacology, 2022)
Background: ASPP2 plays an important role in regulating cell apoptosis and autophagy in liver injury, but the molecular mechanism of ASPP2 regulating autophagy and apoptosis is still unclear. Methods: A hepatocyte injury model was induced using HL7702 cell line by TNF-α. The cells was treated by ASPP2 overexpression adenovirus or short hairpin RNA lentivirus and endoplasmic reticulum stress (ERS) or mammalian target of rapamycin (mTOR) inhibitor or agonist, respectively. The autophagy was detected by western blot and GFP-LC3 plasmid transfection. The apoptosis was detected by western blot, flow cytometry and TUNEL assay. The ERS and mTOR related proteins were detected by western blot. Results: Low ASPP2 expression accompanied by high level autophagy and low level apoptosis and vice versa in hepatocyte injury induce by TNF-α. ASPP2 upregulated the mTORC1 and ERS related proteins, and induced apoptosis but inhibited autophagy. The effect of ASPP2 on autophagy and apoptosis can be reversed by mTORC1and ERS interfering agent, which indicated that ASPP2 regulated autophagy and apoptosis through mTORC1and ERS pathway. ERS treatment had no effect on the expression of ASPP2 and mTOR related proteins which suggested that the regulation of ERS on apoptosis and autophagy maybe in the downstream of ASPP2 and mTOR. Conclusion: ASPP2 inhibits autophagy and induces apoptosis through mTORC1-ERS pathway in hepatocyte injury induce by TNF-α. The role of ASPP2-mTORC1-ERS axis is verified in hepatocyte injury, which suggested that ASPP2 may be an important regulatory molecule in hepatocyte survival and death.